Effect of Cognitive-behavioral Group Therapy on Anxiety and Depression Hemodialysis Patients in Kashan, Iran - A Ahmadvand; R Saie; Z Sepehrmanesh; AR Ghanbari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2011)
Background and Objectives: Hemodialysis as a treatment manner in chronic renal failure is a stressful process and has several various psycho-cognitive and social complications. The present study evaluated effect of cognitive-behavioral group therapy on anxiety and depression in hemodialysis patients.